The Effectiveness of Food and Physical Activity Patterns on The Reduction of Blood Sugar Levels in The Prediabetes Group - Putri, Enda Silvia; Marniatib,; hyunic, Susi Sriwa; Husnae, Arfah; Elidad, Sukma (International Journal of Psychosocial Rehabilitation, 2020)
Background research was every year 4-9% of people with glucose intolerance will become diabetic. The diagnosis of glucose intolerance is made when blood glucose tests show blood glucose 2 hours after glucose loading (TTGO) between 145-179 mg / dL. The purpose research was to looked the effectiveness of food and physical activity patterns on reducing blood sugar levels in the prediabetes group. Method research was quantitative with quasi-experimental research design, prediabetes group research samples as many as 15 people with accidental sampling technique, data from the research was obtained by using questionnaires and blood sugar levels, data were analyzed using t-dependent test. The results obtained by the average value of blood sugar levels (kgd) before the intervention 161.40 mg / dl decreased to 116.60 mg / dl, and obtained a significant P value (0.001